ANALYSIS OF THE EFFECT OF ENGLISH LANGUAGE SKILLS ON THE EFFECTIVENESS OF COMMUNICATION IN EMERGENCY SITUATIONS ON BOARD SHIPS - Natriya Faisal Rachman; Wahyuni Oktavia; Jaka Septian Kustanto; Teguh Arifianto (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2025)
Throughout maritime history, ships have played a strategic role in international trade routes. Therefore, the proper use of English in ship guidance and navigation is crucial to avoid danger. This study measures the effectiveness of English-language emergency communication among shipping professionals by surveying 285 respondents. The research instrument was a questionnaire with 10 questions on a five-point Likert scale. Descriptive analysis results showed an average score of 4.66 out of 5.00, indicating fairly high communication effectiveness. However, there were variations in scores, suggesting that some sailors still need additional training. These findings underscore the importance of strengthening the maritime training curriculum based on Standard Marine Communication Phrases (SMCP).